2011
DOI: 10.1186/1471-2393-11-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high parity on occurrence of anemia in pregnancy: a cohort study

Abstract: BackgroundStudies that explore the controversial association between parity and anaemia-in-pregnancy (AIP) were often hampered by not distinguishing incident cases caused by pregnancy from prevalent cases complicated by pregnancy. The authors' aim in conducting this study was to overcome this methodological concern.MethodsA retrospective cohort study was conducted in Oman on 1939 pregnancies among 479 parous female participants with available pregnancy records in a community trial. We collected information fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
72
8
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 19 publications
(23 reference statements)
12
72
8
6
Order By: Relevance
“…This finding agrees with a study by Al-Farsi, et al where he found that anaemia in pregnancy was three times higher in high parity women compared with low parity pregnancies. 27 Also, van Eijk et al had found that HIV positivity is an important independent risk factor for anaemia in pregnancy. 28 Another complication of placental malaria is fetal anaemia which is thought to result from the exposure of the fetus to malaria antigens following the damage of the placental barrier.…”
Section: Discussionmentioning
confidence: 99%
“…This finding agrees with a study by Al-Farsi, et al where he found that anaemia in pregnancy was three times higher in high parity women compared with low parity pregnancies. 27 Also, van Eijk et al had found that HIV positivity is an important independent risk factor for anaemia in pregnancy. 28 Another complication of placental malaria is fetal anaemia which is thought to result from the exposure of the fetus to malaria antigens following the damage of the placental barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian Ridayanti (2012), menyebutkan bahwa ibu hamil primigravida yang mengalami anemia kehamilan sebesar 44,6% sedangkan ibu multigravida yang mengalami anemia kehamilan sebesar 12,8%. Hal tersebut disebabkan ibu primigravida belum mempunyai pengalaman untuk menjaga kesehatan kehamilan dari kehamilan sebelumnya karena baru pertama kali hamil (Farsi, 2011).…”
Section: Hubungan Paritas Dengan Kejadian Anemia Pada Ibu Hamilunclassified
“…'nın (25) 2011'de Umman'da 1939 gebede yaptıkları bir çalışmada, yüksek paritenin gebelikte anemi insidansını artırdığını göstermişlerdir.…”
Section: Discussionunclassified